BORING SPONGES DESTRUCTIVE TO ECONOMICALLY IMPORTANT MOLLUSCAN BEDS AND CORAL REEFS IN INDIAN SEAS - Thomas, P A (Indian Journal of Fisheries, 2011)
Systematics, description and distribution are given of 32 species of boring sponges from the Indian seas, the frequency of occurrence of which can vary from time to time as any one or more speci’js can at any lime cause an outburst creating severe havoc in the economically important molluscan and coral bedis and then disappear into a period of quiescent stage, while some others may continue to exhibit moderate incidence without causing any such deleterious effects.